Inflammatory effects of atazanavir/ritonavir versus darunavir/ritonavir in treatment naïve, HIV-1-infected patients. Issue 4 (4th July 2018) - Dentone, Chiara; Di Biagio, Antonio; Cozzi Lepri, Alessandro; Fenoglio, Daniela; Filaci, Gilberto; Lichtner, Miriam; Carrara, Stefania; Giacometti, Andrea; Sighinolfi, Laura; Marchetti, Giulia; Antinori, Andrea; D'arminio Monforte, Antonella; et al.
Abstract : Background: Limited studies have compared the impact of different antiretroviral regimens on soluble markers of inflammation with discordant results. Methods: In this prospective study, treatment naïve HIV-1-infected patients were included if they started their current regimen with atazanavir/ritonavir (ATV/r) (N = 73, Group 1) or darunavir/ritonavir (DRV/r) (N = 85, Group 2) plus tenofovir/emtricitabine. The analysis of IL-6, MCP-1, sCD163, VCAM-1, ox-LDL, and adiponectine was performed on two stored plasma samples, the first prior to antiretroviral therapy initiation and the second one year after initiation. Results: The results of our analysis show a difference in ox-LDL between the two groups with higher mean (SD) values in ATV/r based group 608.5 ± 137.4 versus 519.1 ± 119.6 in DRV/r group, after controlling for baseline levels of ox-LDL as well as other potential confounding factors controlled by means of matching design or linear regression modelling. Conclusions: Our analysis provides further data examining the association between the modulation of vascular inflammatory and of activation markers with specific protease inhibitors-based treatments over one year of exposure to these drugs. The data show little evidence for an association, supporting the notion that antiretroviral regimens has generally poor efficiency in downregulating these soluble markers.